2013
DOI: 10.1371/journal.pone.0084322
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Chromosomally-Integrated Human Herpesvirus 6 in Children with Acute Lymphoblastic Leukemia

Abstract: IntroductionHuman herpesvirus 6 (HHV-6) is a ubiquitous pathogen infecting nearly 100% of the human population. Of these individuals, between 0.2% and 1% of them carry chromosomally-integrated HHV-6 (ciHHV-6). The biological consequences of chromosomal integration by HHV-6 remain unknown.ObjectiveTo determine and compare the frequency of ciHHV-6 in children with acute lymphoblastic leukemia to healthy blood donors.MethodologyA total of 293 DNA samples from children with pre-B (n = 255), pre-pre-B (n = 4), pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Four microliters (approximately 50 ng) of the DNA was mixed with primers and probes in a final volume of 10 l, mixed with an equal volume of 2ϫ Rotor-Gene multiplex PCR kit (Qiagen), and subjected to 40 cycles of amplification. The conditions for detection of HHV-6A/B were described previously (6,35). Primers and probe used are listed in Table 4.…”
Section: Methodsmentioning
confidence: 99%
“…Four microliters (approximately 50 ng) of the DNA was mixed with primers and probes in a final volume of 10 l, mixed with an equal volume of 2ϫ Rotor-Gene multiplex PCR kit (Qiagen), and subjected to 40 cycles of amplification. The conditions for detection of HHV-6A/B were described previously (6,35). Primers and probe used are listed in Table 4.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, individuals with such inherited chromosomally integrated HHV-6 (iciHHV-6) carry a copy of the viral genome in every cell of their body. Diagnosis of iciHHV-6 is easily made by measuring and comparing the relative number of HHV-6 DNA copy per cell either using quantitative PCR (qPCR) and/or digital droplet PCR (9,10). iciHHV-6+ subjects have approximately one million copies per million cells, whereas those that have acquired HHV-6 naturally typically have between 60 and 80 viral DNA copies per million cells (11).…”
mentioning
confidence: 99%
“…Genomic DNA extracted from blood-spotted filters was used for HHV-6 qPCR and droplet digital PCR (ddPCR) analyses. Because iciHHV-6 individuals carry one viral genome copy per cell, identification of subjects with iciHHV-6 is easily made (9,34). The overall prevalence of iciHHV-6 in the CaG cohort was determined, and disease prevalence in subjects with iciHHV-6 was compared with that of subjects without iciHHV-6.…”
mentioning
confidence: 99%
“…Thus, the incidence of ciHHV‐6 in Japan appears to be low in comparison with previous studies in Western countries . Previous studies revealed a similar frequency of ciHHV‐6 between healthy controls and children with acute lymphoblastic leukemia, patients with classical Hodgkin lymphoma, and patients with breast cancer . However, ciHHV‐6 was associated with angina pectoris based on a large‐genome cohort study .…”
Section: Discussionmentioning
confidence: 65%